2019
DOI: 10.1016/j.nicl.2018.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of a high-fat diet to Alzheimer's disease-related decline: A longitudinal behavioural and structural neuroimaging study in mouse models

Abstract: Obesity is recognized as a significant risk factor for Alzheimer's disease (AD). Studies have supported that obesity accelerates AD-related pathophysiology and memory impairment in mouse models of AD. However, the nature of the brain structure-behaviour relationship mediating this acceleration remains unclear. In this manuscript we evaluated the impact of adolescent obesity on the brain morphology of the triple transgenic mouse model of AD (3xTg) and a non-transgenic control model of the same background strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 82 publications
8
43
0
2
Order By: Relevance
“…Similar to our results, prolonged HFD consumption caused mice to be hypoactive, but more anxious in another study [17]. In mice, HFD intake increases the risk of neurological disorders that are characterized by cognitive impairments, most notably AD [18]. The peripubertal period is a critical maturational window that is highly sensitive to external influences, such as that of diet on brain function [19].…”
Section: Discussionsupporting
confidence: 84%
“…Similar to our results, prolonged HFD consumption caused mice to be hypoactive, but more anxious in another study [17]. In mice, HFD intake increases the risk of neurological disorders that are characterized by cognitive impairments, most notably AD [18]. The peripubertal period is a critical maturational window that is highly sensitive to external influences, such as that of diet on brain function [19].…”
Section: Discussionsupporting
confidence: 84%
“…We also found maternal brain anatomy was not substantially impacted by the high-fat diet given over the course of approximately 12 weeks. Our results, conducted on C57Bl6/J mice, were consistent with results from Rollins et al, who found that 16 weeks of high-fat diet (60% calories from fat) were needed before adult mice (C57Bl6/J x 129S1/SvImJ strain) had a neuroanatomical phenotype detectable by MR imaging [30].…”
Section: Discussionsupporting
confidence: 92%
“…On the whole, the behavioral, histopathological, and molecular data above suggest that the APP/PS1 mice on the high fat diet in this study showed a similar exacerbation of Alzheimer'srelated effects as in previous studies [16,17,22]. We next sought to determine the role of capillary stalling and CBF deficits in this Hfd-linked exacerbation of Alzheimer's related symptoms.…”
Section: Data Visualization and Statistical Analysissupporting
confidence: 62%
“…Several studies have reported that feeding mouse models of APP overexpression a high fat diet leads to more severe short-term memory deficits [17,22,44]. In our work, we did not observe poorer short term memory function in APP/PS1 mice on a Hfd, as compared to normal chow, perhaps reflecting the sensitivity of the memory tests used here or reflecting differences in the composition, time of onset, duration of administration of the Hfd, or the control diet, as compared to other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation